Diurnal regulation of RNA polymerase III transcription is under the control of both the feeding–fasting response and the circadian clock - Mange, François (Genome Res, 2017)
RNA polymerase III (Pol III) synthesizes short noncoding RNAs, many of which are essential for translation. Accordingly, Pol III activity is tightly regulated with cell growth and proliferation by factors such as MYC, RB1, TRP53, and MAF1. MAF1 is a repressor of Pol III transcription whose activity is controlled by phosphorylation; in particular, it is inactivated through phosphorylation by the TORC1 kinase complex, a sensor of nutrient availability. Pol III regulation is thus sensitive to environmental cues, yet a diurnal profile of Pol III transcription activity is so far lacking. Here, we first use gene expression arrays to measure mRNA accumulation during the diurnal cycle in the livers of (1) wild-type mice, (2) arrhythmic Arntl knockout mice, (3) mice fed at regular intervals during both night and day, and (4) mice lacking the Maf1 gene, and so provide a comprehensive view of the changes in cyclic mRNA accumulation occurring in these different systems. We then show that Pol III occupancy of its target genes rises before the onset of the night, stays high during the night, when mice normally ingest food and when translation is known to be increased, and decreases in daytime. Whereas higher Pol III occupancy during the night reflects a MAF1-dependent response to feeding, the rise of Pol III occupancy before the onset of the night reflects a circadian clock-dependent response. Thus, Pol III transcription during the diurnal cycle is regulated both in response to nutrients and by the circadian clock, which allows anticipatory Pol III transcription.